2017
DOI: 10.12693/aphyspola.131.842
|View full text |Cite
|
Sign up to set email alerts
|

LSMO/YBCO Heterostructures and Investigation of "Negative" Resistance Effect in the Interface

Abstract: Samples containing the ferromagnetic manganite La0.67Sr0.33MnO3 (LSMO) and high temperature superconducting YBa2Cu3O7 (YBCO) single thin film areas and YBCO/LSMO bilayer area were prepared on LaAlO3 (LAO) substrates and were used for investigation of the electrical properties of the interface. The measurements in the YBCO/LSMO interface demonstrated "negative" values of the resistance. A good interpretation of the obtained results was performed in the framework of a 1D model, which took into account the resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Such a property can arise in junctions when the resistance of the barrier (in our case, the interface resistance R IF ) is lower than the resistances of the adjacent YBCO and LSMO layers (R S and R F , respectively). A negative value of the junction resistance R J measured by the 4-probe method was first reported by Giaever [12]; we recently analyzed one in more detail for a LSMO/YBCO interface [13]. Our analyses showed that in the case of superconducting YBCO (R S = 0), the junction resistance measured should always be positive.…”
Section: Resultssupporting
confidence: 51%
“…Such a property can arise in junctions when the resistance of the barrier (in our case, the interface resistance R IF ) is lower than the resistances of the adjacent YBCO and LSMO layers (R S and R F , respectively). A negative value of the junction resistance R J measured by the 4-probe method was first reported by Giaever [12]; we recently analyzed one in more detail for a LSMO/YBCO interface [13]. Our analyses showed that in the case of superconducting YBCO (R S = 0), the junction resistance measured should always be positive.…”
Section: Resultssupporting
confidence: 51%